Assessment of water quality using organic matter Indicators in the downstream Dingin River Wosi Watershed and Pami River, Manokwari West Papua - Gandi Purba; Jemmy Manan; Roy R. Wararomi (Universitas Malikussaleh, 2026)
This study was carried out in Mei 2023 at Dingin River Wosi, West Manokwari District and Pami River, North Manokwari District, both located in Manokwari Regency, West Papua Province. The main objective was to assess the water quality status of Dingin River and Pami River using selected physical and chemical parameters. Based on these assessments, the pollution status (Pollution Index) of each river was determined. An observational approach was used, involving the collection of data through both direct and indirect observations of relevant environmental factors. The results for Dingin River (Wosi) indicated that physical parameters, specifically temperature and turbidity, were within acceptable limits, suggesting good water quality; however, an odor was detected. Chemical parameters—including pH, salinity, dissolved oxygen (DO), biochemical oxygen demand (BOD), and total suspended solids (TSS)—were also within permissible levels, indicating a generally good status. Nevertheless, ammonia concentrations were found to be elevated, while phosphate and nitrate levels remained within acceptable limits. For Pami River, physical parameters were also within acceptable ranges, and no odor was detected. Chemical parameters, including pH, salinity, DO, and BOD, were classified as good, but TSS levels were elevated. Concentrations of ammonia, phosphate, and nitrate were within permissible limits. Based on these findings, the Pollution Index for both Dingin River Wosi and Pami River indicates a category of light pollution. The results of this study are expected to serve as a reference for relevant authorities in evaluating and improving river management strategies to prevent further environmental degradation. Keywords: Organic Matter; Parameters; Water Quality; Watershed Physical; Watershed Chemical Parameters